The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1055/s-0038-1676654
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Riluzole on Cisplatin-induced Ototoxicity

Abstract: Introduction Riluzole (2-amino-6-trifluoromethoxy benzothiazole) is known as a neuroprotective, antioxidant, antiapoptotic agent. It may have beneficial effects on neuronal cell death due to cisplatin-induced ototoxicity. Objective To evaluate the effect of riluzole on cisplatin-induced ototoxicity in guinea pigs. Methods Twenty-four guinea pigs, studied in three groups, underwent auditory brainstem response evaluation using click and 8 kHz tone burst stimuli. Subsequently, 5 mg/kg of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“… 30 Numerous pathways are believed to trigger the apoptosis of cochlear cells through ROS activity, such as the caspase-dependent pathway, caspase-independent pathway, lipid autoxidation, and induction of Ca 2+ influx. 31 Lipid peroxidation (autoxidation) is a chain reaction which continuously provides the supply of peroxide-free radicals and initiates the next peroxidation in the lipoprotein membrane by ROS; among which MDA belongs. 32…”
Section: Discussionmentioning
confidence: 99%
“… 30 Numerous pathways are believed to trigger the apoptosis of cochlear cells through ROS activity, such as the caspase-dependent pathway, caspase-independent pathway, lipid autoxidation, and induction of Ca 2+ influx. 31 Lipid peroxidation (autoxidation) is a chain reaction which continuously provides the supply of peroxide-free radicals and initiates the next peroxidation in the lipoprotein membrane by ROS; among which MDA belongs. 32…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported a prevalence of ALS between 4.1 and 8.4 per 100,000 people. In addition, a difference in ALS prevalence by ethnicity was reported in the United States [ 53 ]. Consequently, the need to find new alternatives to the current single treatment using riluzole is becoming increasingly urgent in order to treat ALS-affected patients.…”
Section: Treatments Against Chronic Neurodegenerative Disordersmentioning
confidence: 99%